A Longitudinal Evaluation of Wraparound's Impact on Youth Mental Health Service Use. (September 2020) - Cosgrove, John A.; Lee, Bethany R.; Unick, George J.
Wraparound is a care coordination model that has shown effectiveness for serving children and youth with significant emotional and behavioral health needs and their families. The current study evaluates a statewide wraparound demonstration with the goals of reducing the use of residential care and increasing access to outpatient mental health services among youth at risk of residential placement. More than 5 years of linked public systems data were analyzed using longitudinal panel data modeling to estimate wraparound treatment effects on service use over time. Findings show that wraparound enrollment decreased the use of residential treatment and increased the use of outpatient therapy, consistent with the goals of the demonstration. Implications are discussed for wraparound's effectiveness as a statewide care coordination model, the importance of quality implementation of wraparound, and the current study's methodological contributions to the wraparound literature.